Non-linearity and/in Translation: On Complex Strategies in the Ukrainian Rendition of Joyce’s Novel-Hypertext “Ulysses” - Bondarenko, Mariia (Respectus Philologicus, 2019)
[full article and abstract in English]By positing that translation is the main manifestation of “interliterarity” (in D. Ďurišin’s conceptualization) that brings to the fore the meta-creational capacities of the target literature, the present article attempts (1) to study a translatability potential of a hypertext as based on the Ukrainian translation of James Joyce’s novel-hypertext Ulysses, and (2) to justify the role of its reception in the Ukrainian literary field as a force for language and culture development. The synthesis of a “verbal music” with a mosaic of texts and narratives – imitated, playfully transformed or directly quoted – is claimed to be a key source of hypertextuality in Ulysses. In this line of reasoning, the paper particularly focuses on (1) the role of both overcoming cultural barriers and leaving a space for reader’s co-creativity while transferring of intertexts; (2) the approaches to interpretation of parody and pastiche as forms of writing-as-translation practice; (3) J. Wawrzycka’s concept regarding translation of musicalized fiction as trans-semantification, i. e. attending to literariness of the text; (4) the idea of translator’s visibility attributed to the Ukrainian re-languaging of musicalized fiction.
Keywords: James Joyce; hypertextuality; intertextuality; verbal music; literary translation